Cultural Exchange and Resilience: Shaping Coffee Consumption in Saudi Arabia's Coffee Shops - Kurniawan Arif Maspul (CV. ULIL ALBAB CORP, 2023)
The impact of cultural variety on coffee consumption habits in Saudi Arabia is investigated in this study, which focuses on coffee shops in Riyadh, Jeddah and Eastern Province. The study wants to know how cultural influences impact coffee culture and what it means for company resilience; provides insights for coffee shop owners to navigate the shifting market climate while promoting cultural interaction and appreciation by examining the relationship between cultural diversity, coffee consumption, and resilience. The research employs a qualitative case study technique, with in-depth interviews with coffee shop owners, employees, and customers, as well as observation of coffee shop settings. The collected data will be evaluated thematically to uncover patterns and insights; considered ethical factors to improve awareness of cultural influences in the coffee business and foster cultural interchange. The findings show that cultural variety has substantially enriched Saudi Arabia's coffee culture, leading to the emergence of inclusive coffee shops that cater to a wide range of tastes and preferences. The presence of people from different countries has allowed product innovation, cross-cultural collaboration, and information sharing in the coffee industry. Inclusive coffee shops also contribute to social cohesion by providing areas for cultural appreciation and understanding. The study emphasizes the significance of cultural variety in shaping coffee consumption patterns and building company resilience. Coffee shop owners and stakeholders can use these findings to develop inclusive coffee cultures that highlight the richness of Saudi society; contributing to the field of cultural studies by underlining the importance of cultural diversity in determining consumption patterns, increasing social cohesion, and enhancing corporate resilience in the coffee value chain.